PROFILE OF ACNE VULGARIS PATIENTS AT BETHESDA HOSPITAL YOGYAKARTA FROM JULY 2019 to DECEMBER 2020 - Yoshe Ivana Putri; Arum Krismi; Gabriel Erny Widyanti (Berkala Ilmiah Kedokteran Duta Wacana, 2023)
Background Acne vulgaris is a chronic inflammatory disease of the pilosebaceous follicles. This disease is usually found in more than 85% of young adults worldwide. Acne vulgaris can cause psychological morbidity and also greatly affects socio-economic and the quality of life. Patients often have already tried several treatments, but still do not get good results. Therefore, it is important to identify the type of lesion and then choose the right treatment for acne vulgaris. Objective To know the profile of acne vulgaris patients at the Dermatology and Venereology Clinics of Bethesda Hospital Yogyakarta, from July 2019 to December 2020. Methods This study was a descriptive-retrospective study, using secondary data from the medical records of acne vulgaris patients. Data will be collected in the percentage frequency distribution table. Results This research was done in the medical records department of Bethesda Hospital Yogyakarta from February to April 2022. The number of samples taken by total sampling technique that matched the inclusion and exclusion criteria was 151 records. The highest percentage of acne vulgaris patients were female 72.2% (109 people), aged 20-24 years 57.0% (86), had inflammatory skin lesions 54.3% (82), received combination of topical and systemic treatment 80.8% (122), the most topical treatment prescribed was niacinamide 80.8% (122), the most systemic treatment was antibiotics 41.7% (63), the most systemic antibiotic was minocycline 73.0% (46), the highest visiting frequency was once (without control) 57.6% (87), and irregular follow-up visits 60.9% (92). Conclusion Based on the study conducted, patients with acne vulgaris were dominated by females, aged 20-24 years. One of the most prominent symptoms was inflammatory skin lesions. The patients have received combinations of topical and systemic treatment. The most used topical treatment was niacinamide; the most used systemic treatment was antibiotics; and the most used systemic antibiotic was minocycline. The highest trend for visiting frequency were irregular controls followed by one-time doctor visit without control. Keywords: Acne Vulgaris, Demography, Therapeutics, Control